Flood mapping of the lower Mejerda Valley (Tunisia) using Sentinel-1 SAR: geological and geomorphological controls on flood hazard - Khemiri, Lamia; Katlane, Rim; Khelil, Mannoubi; Gaidi, Seifeddine; Ghanmi, Mohamed; Zargouni, Fouad (Frontiers in Earth Science, 2024)
During the last decade, the Mejerda Valley in Tunisia has experienced several major flood events despite the prevailing drought conditions in North African countries. This study explores the use of Sentinel-1 radar data for the detection and management of floods in the region. Sentinel-1 radar data provide continuous monitoring capabilities independent of weather conditions, making them highly effective for tracking the evolution of floods over time and accurately mapping the extent of affected areas. To create classified flood images, a specific formula was applied to represent water objects by assigning a value of 255 to water objects while lowering the backscattering threshold to 2.22E-2. This formula generated a logical "true" value (1) for values below 2.22E-2 and "false"(0) for higher values. The resulting image represents water objects with a value of 255, while other areas are set to 0. Several major flood events in the Mejerda Valley, including the floods of 2015, 2017, 2019, and 2020, are discussed. These events significantly impacted various regions, with precipitation reaching up to 141mm during the 2015 floods. Furthermore, this study highlights the implications of river regulation, such as dam construction, on flood risk. Changes in the hydrological regime, encompassing both the duration and spatial extent of floods, can have significant consequences. The study focuses on the geological and geomorphological history influences on the lowland plain of the Mejerda Valley vulnerability to annual floods.